Measurements of ion mobility in argon and neon based gas mixtures - Deisting, Alexander; Vranic, Danilo (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
As gaseous detectors are operated at high rates of primary ionisation, ions created in the detector have a considerable impact on the performance of the detector. The upgraded ALICE Time Projection Chamber (TPC) will operate during LHC Run 3 with a substantial space charge density of positive ions in the drift volume. In order to properly simulate such space charges, knowledge of the ion mobility K is necessary. To this end, a small gaseous detector was constructed and the ion mobility of various gas mixtures was measured. To validate the corresponding signal analysis, simulations were performed.